Efficacy of Percutaneous Herbert screw fixation for treating delayed union and nonunion of the Scaphoid. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the radiological outcome of percutaneous Herbert screw fixation in delayed union and nonunion of the Scaphoid.Methods: This descriptive study was conducted in National orthopedic and General Hospital Bahawalpur from 20th February 2018 to 20th March 2022.All adults patients with Scaphoid delayed union and non fulfilling the inclusion criteria were treated with percutaneous Herbert screw fixation without bone grafting. Post operative radiographic union was determined at five months.Results: The data of 9 patients fixed with percutaneous Herbert screw fixation were analyzed. All patients were male with mean age of 26±5 years. Delayed union was present in 5(55.55%) patients and non union in 4(44.44%). All fractures achieved radiological union in 15.5±4.2 weeks. Postoperative wrist stiffness was noted in 2(22.22%) patients and was treated with physical therapy. No patient required revision surgery.Conclusion: Delayed union and nonunion of the Scaphoid can be treated successfully with Percutaneous Herbert screw fixation as shown by excellent radiological union in all of our cases.